LAPAROSCOPIC SUBTOTAL CHOLECYSTECTOMY AT ACUTE CHOLECYSTITIS - Bychkov, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
A new method of the laparoscopic subtotal cholecystectomy it is developed.Its efficiency is confirmed on 30 experimental rabbits of the sort Chinchillas. Author offers his experience of laparoscopic subtotal cholecystectomy execution at 34 patients with acute cholecystitis. The analysis of results of experimental researches showed safety and efficiency of the laparoscopic subtotal cholecystectomy application with the cryodestruction of mucous membrane of remaining part of back wall of gall-bladder.